1970
DOI: 10.1007/bf02541455
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids of long chain length in baltic herring lipids

Abstract: The component fatty acids with carbon numbers exceeding 22 in flesh lipids of Baltic herring caught in May and September 1967 in the Turku archipelago have been studied. The total lipid content of the flesh of the herring was 3.5% on average in May and 7.2% on average in September. The fatty acids in the lipids were converted to methyl esters which were resolved and analyzed by urea adduct fractionation, thin layer chromatography and programmed temperature gas liquid chromatography (GLC). The lipids of the her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 9 publications
3
19
0
Order By: Relevance
“…In particular, the increase in blood adiponectin levels was the lowest in the EPA treatment group and the highest in the DHA treatment group; therefore, DHA is thought to be the most effective n-3HUFA for the suppression of metabolic syndrome, diabetes, and atherosclerotic progression. Tetracosapentaenoic acid THA, 24:6n-3 is an n-3HUFA that is also found in fishes, including the Baltic herring Clupea harengus 13 , and flathead flounder Hippoglossoides dubius 14 . THA is also found in the brittle star Amphiura elandiformis 15 and in jellyfish Aurelaia sp.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the increase in blood adiponectin levels was the lowest in the EPA treatment group and the highest in the DHA treatment group; therefore, DHA is thought to be the most effective n-3HUFA for the suppression of metabolic syndrome, diabetes, and atherosclerotic progression. Tetracosapentaenoic acid THA, 24:6n-3 is an n-3HUFA that is also found in fishes, including the Baltic herring Clupea harengus 13 , and flathead flounder Hippoglossoides dubius 14 . THA is also found in the brittle star Amphiura elandiformis 15 and in jellyfish Aurelaia sp.…”
Section: Introductionmentioning
confidence: 99%
“…1) exhibited a molecular ion at m/z 435. The presence of 12 unit intervals at m/z 180-192, 220-232, 260-272, 300-312, 340-352 and 380-392 revealed the positions of double bonds at 8,11,14,17,20 and 23 carbon atoms. The position of a double bond at Δ5 showed a characteristic peak at m/z 153 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[7]. Only limited data are available pertaining to the presence of FA with 26 carbon atoms in marine animals [8][9][10][11][12][13]. In a comparative investigation of lipids in symbiotic and nonsymbiotic brittle stars, McKenzie et al [11] found a series of PUFA with 24 and 26 carbon atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Aquatic organisms also contain VLCPUFA [13]. Baltic herring include those up to C28 [14][15][16], some of which are represented in the fatty acids of the predatory ringed seal [17]. Bottom-living flathead flounder is rich in 24:6n-3 [18,19], which presumably originated from their diet of brittle star [20][21][22].…”
Section: Introductionmentioning
confidence: 99%